Reconhecimento do talento em alunos com perdas auditivas do ensino básico - Rangni, Rosemeire de Araújo (Universidade Federal de São Carlos, 2012)
The thematic of talent is accepted among the special educational needs (SEN) since the 70 s when it was at the Lei de Diretrizes e Bases da Educação Nacional for the first time. This group of students hasn t received appropriated educational answers to their SEN that have been confirmed by the low dates from the school census. On the other hand, the disabled students are put with more emphasis in the special educational services at the common schools and special educational institutions. The students who present two SEN - disabilities or syndromes - can receive the services in the multiple disabilities. The students with twice special educational needs (TSEN), talent and hearing loses, aren t recognized by their abilities. The recognition of TSEN talent and hearing loses -, specifically at common schools, get a hard way in the inclusion process for the disabled students. This process involves others professionals as Libras interpreters, and specialists who works in the special rooms . This study aims to recognize the students with talent and hearing loses included at common schools. For this, the study was Exploratory and Case Study. Fifty-two (52) students took part of the study from both genders, and various grades of hearing lose enrolled in the junior high school and high school. Two schools were selected in the public system: School A (13 students enrolled in the state public school in the countryside of São Paulo); School B (29 students enrolled in the municipal system) located in the metropolitan area of São Paulo). The obtained results were: 1) Two (2) students were indicated at the School A, and 2) Four (4) students were indicated at the School B. For this, it s wished the results are traces for future studies to refine the gifted and talented students indications with hearing loses or others SEN. Also the indicated students don t get in the statistic dates only to increase them but the students receive educational services to develop their potentials.
Recognition of talent in students with hearing loses in common schools
Keywords: Educação especial; Superdotação; Altas habilidades; Talentos; Perda auditiva; Educação inclusiva; Special Education; Talent; Hearing loses; Inclusive Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL